KANTONG SEMAR PEMBANGKIT IDE BERKARYA DALAM LUKISAN BATIK DAN SULAM - Andi Tanamal; Erwin Erwin (Universitas Negeri Padang, 2021)
Katong Semar generates ideas in the creation of the final work which aims to visualize unique plants through painting with batik and embroidery techniques. The creation of this final work is expected to introduce this one plant to many people. The creation of this work through several methods, including: preparation, elaboration, synthesis, concept realization, and completion. The embodiment of this idea is summarized in 10 works with the title: 1)Sicantik Yang Laper 2)Kancung Beruk 3)Feminim 4)Sulung 5)Terpikat 6)Sisemar 7)Menjalar 8)Menggantung 9)Menipis 10)Semestinya.Kata kunci: Kantong Semar,Lukis,Batik dan Sulam